Human rights among Korean dental hygiene students in hospital clinical practice - Yoon-Ah Won; Hie-Jin Noh (BMC Medical Education, 2024)
Abstract Background The human rights of dental hygiene students should be guaranteed during practice at medical institutions for their mental and physical health as well as professionalism, for patient safety. Safe and well guaranteed clinicians can perform their work in a more stable way. This study investigated the human rights circumstances of dental hygiene students during their hospital clinical practice at dental institutions. Methods This study used a cross-sectional survey design. Convenience sampling was conducted on 121 third- and fourth-year dental hygiene students from universities in Seoul, Gyeonggi, and Gangwon. The survey used the Human Rights Indicators for Dental Hygiene Students to investigate the rights to safety, equality, and personality to understand participants’ experiences of guaranteed fundamental rights. Data were collected from October 31 to November 8, 2019. A chi-square test was used to assess differences in experience according to general characteristics. Results During dental hygiene practice at dental institutions, less than 50% of students felt safe. When human rights violations occurred in dental institutions, only 42.4% of students received guidance on response measures from their universities. While 72.1% of students who practiced at dental university hospitals were given information on first aid supplies (facilities) within dental institutions, only approximately 45% of students who practiced at lower-scale dental institutions were given this information (p < 0.05). Regarding equality rights, only 52.5% of trainees reported that they had received equal treatment from healthcare workers during hospital clinical practice. Conclusions During dental practice at dental institutions, Korean dental hygiene students confirmed that human rights (including safety rights, equality rights, and personality rights) were guaranteed to varying degrees. Dental hygiene students’ rights during hospital clinical practice in dental institutions should be guaranteed across institutions regardless of their scale. This is necessary for dental hygiene students’ human rights and safe policies and guidelines in dental institution clinical practice and regular monitoring systems.